DEVELOPMENT OF SERVICES COMPUTING SYSTEMS ENGINEERING METHODOLOGY BASED ON SERVICE ORIENTED ARCHITECTURE - Budi Kurniawan, Novianto
Research of service computing in the last 10 years has benefited the organization in using and applying service computing technology to improve its service system. The development of service computing technology sparked the need of organizations in building a service computing system that has capability for delivering IT services that can meet the requirements of business services. Through service computing technology, service innovation can be achieved by the organizations to improve service productivity and quality. Research in service design areas are a key challenge in service computing research. The understanding and knowledge of service design is essential as a prerequisite for developing the service system. The challenges in the service design area are crucial along with the application of service computing to the organizations for seeking and require the optimized services computing systems engineering methodology to realize the design of the systems.